2021
DOI: 10.1080/09638288.2021.1979663
|View full text |Cite
|
Sign up to set email alerts
|

Being a parent of a child with Down’s arthritis: an interpretative phenomenological analysis

Abstract: Purpose: To explore the parental impact and experiences of caring for a child with Down's arthritis (DA), an aggressive, erosive form of arthritis affecting children with Down syndrome. Materials and methods: Ten mothers of children with DA were interviewed via telephone. Interviews were guided using a semi-structured non-directive topic guide and ranged from 17 to 242 minutes in duration. Interpretative phenomenological analysis was the method of analysis. Results: Three superordinate themes were identified: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Six studies were categorized as negative/problem focused. The study by McDonagh et al (2021) is an example of a study that is negative/problem focused. Semi-structured interviews were conducted with 10 mothers living in the Republic of Ireland who have a child with DS who also has arthritis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies were categorized as negative/problem focused. The study by McDonagh et al (2021) is an example of a study that is negative/problem focused. Semi-structured interviews were conducted with 10 mothers living in the Republic of Ireland who have a child with DS who also has arthritis.…”
Section: Resultsmentioning
confidence: 99%
“…Across the 41 studies, researchers collected data from 5,989 respondents ( Table 5 ), 4,438 (78%) of whom were the child’s mother, with 9 studies focusing exclusively on mothers ( Alabri, 2023 ; AlJameel & AlKawari, 2021 ; AlJameel et al, 2020 ; Cless et al, 2017 ; Finkelstein et al, 2021 ; Jess et al, 2021 ; Korkow-Moradi et al, 2017 ; McDonagh et al, 2021 ; Pruktarat et al, 2021 ). Fathers were included in 29 studies and were the exclusive focus of two studies ( Pisula & Banasiak, 2020 ; Sheldon et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Others have also shown that families often are unaware that their child is displaying signs of arthritis, 8 and many present to care several times with inflammatory arthritis symptoms prior to a diagnosis of DA. 41 Even after diagnosis of DA, families report emotional, physical and financial challenges of being a parent and caregiver to an individual with intellectual disability and additional complex chronic disease 42 that affects mobility and requires immunosuppressive therapy in the setting of increased risk of infection. Other challenges to diagnosis of DA include musculoskeletal findings specific to individuals with DS such as hypotonia, ligament laxity and delayed motor skills that may mask signs of inflammatory arthritis.…”
Section: Evaluation Of Down Syndrome-associated Arthritismentioning
confidence: 99%